Melodies of Spiritual Songs from Ethiopia - Nilsson, Marianne (Sweden.: : Marianne Nilsson Bokfr̲lag, 2019)
Around 300 songs from Ethiopia, written down in music and described in musical terms, are found in this book. The songs were composed in the 1970s, the first decade of new-composed spiritual songs with lyrics in Amharic sung on Ethiopian melodies.
Keywords: Spiritual Songs; Hymns, English; Christian church Public worship